Risk management for design and construction - Cretu, Ovidiu; Stewart, Robert, 1968-; Berends, Terry (Hoboken, N.J. : RSMeans, 2011)
'This text provides a balance of theory, technique and facilitation. The emphasis is on providing a practical and proven framework for risk management on real projects with a clear, concise description of the complex topic of risk for professionals. Written by two experts in the field, it offers a practical, proven means of quantifying and minimizing risk, to inform business decisions in the design and construction field. Case studies and examples on the proper application of software and principles help make this book an important reference to the field'--
'The book presents an integrated approach to cost and schedule for qualitative risk analysis. This approach recognizes the value of considering the project schedule when cost is estimated. The approach was created and developed at the Washington State Department of Transportation (WSDOT). The authors have expanded the scope of the process to cover any type of construction, and have provided two case studies developed throughout the book presenting the process in use on an instutional construction project and a heavy civil construction job'--
Machine generated contents note: Preface. -- Acknowledgements. -- Chapter 1. Introduction. -- Chapter 2. Project Cost and Schedule Estimates. -- Chapter 3. Risk Based Estimate (RBE). -- Chapter 4. Risk Elicitation. -- Chapter 5. Risk Management. -- Chapter 6. Risk Based Estimate Self-modeling Spreadsheet (RBES). -- Chapter 7. Risk Based Estimate Workshop.
Includes bibliographical references and index.
Keywords: Building -- Safety measures; Construction industry -- Accidents -- Prevention; Construction industry -- Risk management